Citizen Journalism Berbasis Komunitas: Optimalisasi Tunasmalang.id sebagai Portal Berita Persyarikatan Muhammadiyah Kota Malang - Sujoko, Anang; Prianti, Desi Dwi; Wahyudi, Dicky; Hurriyah, Nur Khulailatul (Universitas Muhammadiyah Surakarta, 2024)
Tunasmalang.id as an online news portal from PDM (Pimpinan Daerah Muhammadiyah) Malang City has not functioned optimally due to a lack of human resources for news production and a simple website display. This community service program aims to optimize the online news portal Tunasmalang.id through a citizen journalism approach and improve its website so that it represents PDM Malang City. The method used journalism training with a learning by doing system, and improves the appearance of the Tunasmalang.id website. This community service succeeded in forming citizen journalist contributors who came from members of the Muhammadiyah Autonomous Organization throughout Malang City, who producting news content on Tunasmalang.id. The presence of citizen journalist contributors has increased the quantity and variety of news content on Tunasmalang.id. Website improvements give Tunasmalang.id a different appearance from before, and the Tunasmalang.id website can represent PDM Malang City. Community service states that the citizen journalism approach does not only function for the development of Tunasmalang.id as an online news portal, but can also empowering members of the Muhammadiyah Autonomous Organization throughout Malang City to become citizen journalists. The citizen journalism approach and improving the appearance of the website make Tunasmalang.id is a man of extension that delivers information about PDM Malang City and the reality that is happening in society.